The Innovation of Multimedia-Based Arabic Language Learning - Faisal Mubarak, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Arabic Language is one of the subjects that must be taught at Islamic School. It is expected that the graduates have basic skills in Arabic, both speaking and writing. However, the results were still far from what expected. The low quality of Arabic language acquisition cannot be separated from the negative perception that Arabic language is difficult and complicated to learn. This is because the material is abstract, not delivered with concrete and practical approaches, models, methods, and learning media. This study used a Research and Development approach or strategy. The developed learning model design consisted of objectives, materials, methods, and evaluation. The materials were packed in the form of a CD consisting of power points, videos, animations, pictures, and texts, supported by audio. The developed learning model in this study has proven to be more effective than Arabic learning that has been going on so far. The results can be seen from the results of the validation test involving the experimental and control groups. Based on the results, the average score of the experimental group was higher than of the control group.